A feasibility study for recording of dispensing errors and near misses' in four UK primary care pharmacies - Chua, S.S.; Wong, I.C.; Edmondson, H.; Allen, C.; Chow, J.; Peacham, J.; Hill, G.; Grantham, J. (2003)
Medication errors can occur at the prescribing, transcription, dispensing and administration stage of drug therapy. However, publication of the Organisation with a Memory (OWAM) by the Department of Health in the UK has raised awareness of the need for pharmacies to collect information about dispensing errors and near misses, which occur within an organisation. Such information provides valuable insights into the vulnerabilities of dispensing procedures and identifies areas for improvement in dispensing systems The main aim of this study was to investigate the feasibility of a self-reporting system for dispensing errors and near misses in primary care (community) pharmacies. It was also to identify the types of errors or near misses commonly encountered in community pharmacies. A data collection form was designed and modified for use after a pilot study. Four community pharmacies volunteered to participate in this feasibility study. The data collection was conducted in two phases each of 4 weeks' duration. Any dispensing errors and near misses that occurred during the study periods were recorded by the pharmacy staff in a standard data collection form. A focus group discussion was held with the dispensing staff of participating pharmacies to identify and evaluate the feasibility of the reporting system. Out of a total of 51 357 items dispensed during the two phases of the study, 39 dispensing errors (0.08) and 247 near misses (0.48) were detected. The results show that near misses occurred six times more often than dispensing errors, indicating the importance of final checking in pharmacies. The most common types of dispensing errors or near misses appeared to be incorrect strength of medication, followed by incorrect drug, incorrect quantity, incorrect dosage form and incorrect label. Feedback during the focus group discussion indicated that the outcome of the self-reporting scheme was more important than the incidence of errors or near misses. Participating pharmacies also agreed that the self-reporting scheme used was feasible and they would continue using the scheme although some incentives would be helpful. The quantitative results of this study and the qualitative feedback from the participating pharmacies indicate that the self-reporting scheme used is practical and feasible.